Peningkatan Skill Pelaku UMKM Dalam Pembuatan Laporan Keuangan di Desa Negari Klungkung - Ida Ayu Ria Paramita Handayani; I Gusti Ayu Putu Eka Dewi Prihantari; Ida Bagus Putra Manuaba; I Gusti Ngurah Putra Harthawan; Putu Diah Krisna Junitasari; Ezra Naibaho (CV. Ulil Albab Corp, 2023)
The people's livelihoods are very diverse and there are several types of MSMEs in Negari Village, making the field of entrepreneurship another potential that can be developed. There are several types of MSMEs in Negari Village including handicrafts from coconut shells, bowls, to kenoveksi screen printing and embroidery. The choice of Desa Negari as a location for community service is based on the existence of several aspects of the problem, namely human resources who still do not fully understand financial reports in managing their business finances. There are still many small entrepreneurs who have not properly recorded their finances. There are even those who do not keep records. Small and medium entrepreneurs usually only do bookkeeping, limited to recording income and expenses. Where this will impact losses and bankruptcy for the MSME actors themselves (Mu'minah, 2019). The approach to community service in Negari Village is carried out by providing training to the community. This is a form of effort to maximize the potential possessed through competency improvement training. Some of the training provided included an understanding of basic accounting, basic knowledge of financial records and training in making financial reports according to standards.